THE EFFECT OF CUSTOMER INCIVILITY ON WORK ENGAGEMENT, MODERATED BY SELF-EFFICACY(A Study at Prama Sanur Beach Hotel, Bali) - Anak Agung Gede Yudha Santaka; I Gede Riana (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2026)
The hospitality industry is characterised by roles involving a high intensity of service interactions; consequently, employees’ psychological engagement in performing their job roles is a crucial factor in maintaining service quality, as reflected in their level of work engagement. This study aims to analyse the effect of customer incivility on work engagement, with self-efficacy serving as a moderating variable. Testing the job demands–resources theory, this study employs a quantitative approach with a causal design. The study population comprises all frontline employees at Hotel Prama Sanur Beach Bali, selected via saturation sampling. Data were collected using a structured questionnaire and analysed using Structural Equation Modelling – Partial Least Squares (SEM-PLS) WarpPLS. The results indicate that customer incivility has a significant negative effect on work engagement. Self-efficacy was found to mitigate the negative impact of customer incivility on work engagement. These findings underscore the importance of strengthening self-efficacy as a personal resource to maintain employee work engagement when facing the emotional demands of the job.